Corrective Ad Valorem and Unit Taxes: A Welfare Comparison - Susanne Dröge; Philipp J. H. Schröder (Deutsches Institut für Wirtschaftsforschung (DIW), 2005)
The ad valorem versus unit taxes debate has traditionally emphasized tax yield. For this criterion, ad valorem taxes outperform unit taxes in terms of welfare for a wide range of imperfect competition settings, including Dixit-Stiglitz monopolistic competition. Yet, in a number of policy fields, such as environmental, health or trade economics, policy makers apply taxes to target the production/consumption volume in an industry, i.e. aim at a certain corrective effect rather than tax yield. This paper compares the two tax instruments with respect to equal corrective-effect in a Dixit-Stiglitz setting with love of variety, entry, exit, and redistribution of tax revenues. We find that unit taxes lead to more firms in the industry, less output per firm, less tax revenue, but higher welfare compared to ad valorem taxes.
Keywords: H23; L13; 330; Externalities; Monopolistic competition; Taxes; Specific Taxes; Welfare